(x+2.1)-(0.1x+3)=11

Simple and best practice solution for (x+2.1)-(0.1x+3)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+2.1)-(0.1x+3)=11 equation:


Simplifying
(x + 2.1) + -1(0.1x + 3) = 11

Reorder the terms:
(2.1 + x) + -1(0.1x + 3) = 11

Remove parenthesis around (2.1 + x)
2.1 + x + -1(0.1x + 3) = 11

Reorder the terms:
2.1 + x + -1(3 + 0.1x) = 11
2.1 + x + (3 * -1 + 0.1x * -1) = 11
2.1 + x + (-3 + -0.1x) = 11

Reorder the terms:
2.1 + -3 + x + -0.1x = 11

Combine like terms: 2.1 + -3 = -0.9
-0.9 + x + -0.1x = 11

Combine like terms: x + -0.1x = 0.9x
-0.9 + 0.9x = 11

Solving
-0.9 + 0.9x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '0.9' to each side of the equation.
-0.9 + 0.9 + 0.9x = 11 + 0.9

Combine like terms: -0.9 + 0.9 = 0.0
0.0 + 0.9x = 11 + 0.9
0.9x = 11 + 0.9

Combine like terms: 11 + 0.9 = 11.9
0.9x = 11.9

Divide each side by '0.9'.
x = 13.22222222

Simplifying
x = 13.22222222

See similar equations:

| x-10403=116 | | 5b=3.55 | | -22+6x=44-5x | | 4x-5=4x+7 | | 4x+5=4x+5 | | 3/2a-14=75 | | (x+2.7)-(0.3x+4)=11 | | -15-v=-24 | | y-2=5/4x | | 6(5-x)-12=2x-3(4+x) | | y=0.25x+21 | | 5n+20=n-24 | | 3p-6=13-4p | | 3(2x+5)=7-(2x) | | n/17=18 | | Dover-8.4=10.2 | | -11n=-154 | | 62.9296x+64.9278y=63.546 | | 1/8(5x-24) | | x^2+7x+35=0 | | 2/7=1/3+a | | 0.25= | | 1023/80=-3/3/10(-3/2+x) | | 3x+3=-3x-12 | | 3p=8p-r | | b+1/6=65 | | 36-7n=1+3(8-6n) | | =(3x-2) | | 62.9296(1.009795073-1.031752943y)+64.9278y=63.54600003 | | 8m-5(m-2)=7 | | -8+5(1+6c)=-27 | | 62.9296(1.009795073-1.031752943y)+64.9278y=63.5460003 |

Equations solver categories